Graphene oxide polypiperazine-amide nanofiltration membrane for improving flux and anti-fouling in water purification. Issue 85 (30th August 2016) - Wang, Jin; Zhao, Changwei; Wang, Tao; Wu, Zhen; Li, Xiang; Li, Jiding
Abstract : A novel PPA/GO composite nanofiltration membrane with nanomaterial graphene oxide (GO) incorporated into a polyamide (PA) layer for high water flux and anti-fouling was fabricated by interfacial polymerization (IP). Abstract : In this study, a facile polypiperazine-amide (PPA) composite nanofiltration (NF) membrane with nanomaterial graphene oxide (GO) incorporated into a polyamide (PA) layer for high water flux and anti-fouling was fabricated by interfacial polymerization (IP). The chemical composition, structure and surface properties of the fabricated PPA/GO and PPA composite NF membranes were characterized by FTIR, XPS, FE-SEM, AFM, zeta-potential and contact angle measurements. The separation properties and anti-fouling ability of the PPA/GO NF membrane were investigated and discussed. The experimental results indicated that the water flux of the PPA/GO (300 mg L −1 GO) membrane increased from 66 (L m −2 h −1 ) to 87.6 (L m −2 h −1 ) under the operating pressure of 0.6 MPa, almost 1.4 times that of the PPA (without GO) membrane. However, the high salt rejection was still retained in the order of Na2 SO4 (98.2%) > MgSO4 (96.5%) > NaCl (56.8%) > MgCl2 (50.5%). An anti-fouling test revealed that the PPA/GO membrane had excellent anti-fouling properties due to the enhanced hydrophilicity and decreased roughness induced by the GO nanosheets. Thus, the PPA/GO membrane can be efficiently and endurably applied in water purification.